Study of early complications of great saphenous vein stripping in varicose veins surgery - كفى , علي; أحمد , غانم; عبد الله , شاكر (Latakia University Journal -Medical Sciences Series, 2022)
Aim: Study of early complications of great saphenous vein stripping, and determine the methods and techniques that limit or reduce the occurrence of these complications. Methods: A prospective study of 94 patients, who underwent stripping of great saphenous vein (unilateral), their early complications were identified, and they were followed up immediately after surgery and for a month after surgery. Results: The study sample included 94 patients, The percentage of females was (69.1%) and the percentage of males was (30.1%), where the ratio of females to males is (2.2:1). Minor complications occurred in 20 patients, including hematoma (7.4%), sepsis (13.8%), saphenous nerve injury (6.3%), and lymphatic drainage (3.1%). One case of deep vein thrombosis occurred as a major complication (1%). Conclusion: The operation of great saphenous vein stripping is associated with a significant proportion of minor complications; major complications are rare but serious.